The Implementation of the Singing Method in Arabic Language Learning for Early Childhood - Pratiwi, Sindi; Selian, Suci Nadilla; Muhammad, Arfin; Lubis, Hilda Zahra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study explores the application of the singing method in Arabic language education for early childhood, highlighting the need for creative and engaging approaches suitable for young learners. The study positions singing as an effective pedagogical strategy by integrating rhythm and melody to enhance language acquisition. A qualitative-descriptive method is employed in this research, utilizing observations, interviews, and document analysis to collect data. This research investigates how singing can facilitate vocabulary retention, boost motivation, and improve children's understanding. The results indicate that incorporating simple theme-based songs into learning significantly enhances children's enthusiasm and self-confidence while strengthening their cognitive and affective development. These findings contribute to the understanding of innovative methods in early childhood language teaching, emphasizing the practicality and effectiveness of music-based learning in creating a fun and supportive educational environment.